Identifikasi Begomovirus yang Berasosiasi dengan Penyakit Kuning pada Mentimun di Jawa Barat dan Bali - Rizki Haerunisa; Gede Suastika; Tri Asmira Damayanti (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2016)
ABSTRACTA survey conducted from several cucumber cultivation area of West Java and Bali found some plants showing yellow mosaic, vein banding, and stunting symptoms, caused by Begomovirus infection. This study aimed to detect and determine incidence of Begomovirus on cucumber plants, and analyze variation of Begomovirus coat protein gene in West Java dan Bali. Leaf samples from 50 plants were taken randomly from each location in Sumedang, Karawang, Sukabumi (West Java) and Tabanan, Gianyar, Klungkung (Bali). Disease incidence was determined based on serological assay using specific antiserum of Tomato leaf curl New Delhi virus (ToLCNDV) dan Squash leaf curl virus (SLCV). Incidence of ToLCNDV and SLCV were 28-100% and 30-80%, respectively. PCR using Begomovirus degenerate primers successfully amplified coat protein gene about ± 550bp. There were three Begomovirus species associated with yellowing disease on cucumber plant i.e Squash leaf curl China virus (SLCCNV), ToLCNDV, and Ageratum yellow vein virus (AYVV). Based on nucleotide sequences analysis, it was found that isolate SLCCNV had highest nucleotide homology with SLCCNV isolate Malaysia (EF197940) about 94.5%, and was considered as a strain “China”, whereas ToLCNDV has highest nucleotide similarity with ToLCNDV isolate Indonesia (AB613825) about 99.4% and was considered as a strain “Indonesia”. The AYVV sequences showed highest nucleotide AYVV isolate Nicotiana benthamiana from Indonesia (AB100305) about 92.1%.Keywords: Cucumis sativus, Dot immunobinding assay, Squash leaf curl China virus, Tomato leaf curl New Delhi virusABSTRAKSurvei yang dilakukan di beberapa pertanaman mentimun di Jawa Barat dan Bali menemukan gejala mosaik kuning, daun keriting, penebalan tulang daun, dan kerdil akibat infeksi Begomovirus. Penelitian ini bertujuan untuk mendeteksi dan menghitung insidensi penyakit yang disebabkan oleh Begomovirus pada tanaman mentimun, serta menganalisis keragaman gen protein selubung Begomovirus di Jawa Barat dan Bali. Sampel daun diambil secara acak sebanyak 50 tanaman dari tiap lokasi pertanaman mentimun di Sumedang, Karawang, dan Sukabumi (Jawa Barat), Tabanan, Gianyar, dan Klungkung (Bali). Deteksi Begomovirus dan insidensi penyakit ditentukan dengan uji serologi DIBA menggunakan antiserum Tomato leaf curl New Delhi virus (ToLCNDV) dan Squash leaf curl virus (SLCV). Insidensi ToLCNDV dan SLCV berturut-turut berkisar 28-80% dan 30-80%. Deteksi dengan teknik PCR menggunakan primer universal Begomovirus berhasil mengamplifikasi gen protein selubung berukuran ± 550 pb. Hasil perunutan nukleotida menunjukkan terdapat tiga spesies Begomovirus yang menginfeksi tanaman mentimun di Jawa Barat dan Bali, yaitu Squash leaf curl China virus (SLCCNV), ToLCNDV, dan Ageratum yellow vein virus (AYVV). Isolat SLCCNV Bali memiliki kesamaan nukleotida dan asam amino terhadap isolat SLCCNV dari negara lainnya berkisar antara 89.8-94.5% dan 94.2-96.3%, dan dikelompokkan ke dalam strain “Cina”. ToLCNDV isolat Jawa Barat dan Bali memiliki kesamaan nukleotida dan asam amino berkisar antara 92.8-99.4% dan 97.3-99.4% dengan isolat ToLCNDV dari negara lainnya, tergolong ke dalam strain “Indonesia”. Gen protein selubung AYVV Bali memiliki kesamaan nukleotida dan asam amino berkisar antara 89.5-92.1% dan 94.7-95.2%, dengan kesamaan tertinggi dengan isolat AYVV asal Indonesia yang menginfeksi Nicotiana benthamiana.Kata kunci: Cucumis sativus, Dot immunobinding assay, Squash leaf curl China virus, Tomato leaf curl New Delhi virus.